2018
DOI: 10.3855/jidc.10442
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis screening in resource-limited countries – Comparison of diagnostic accuracy of 3 different assays

Abstract: Introduction: Commercially available assays were evaluated in order to determine diagnostic accuracy of Chlamydia trachomatis specific tests for screening. Methods: The study included 225 sexually active men and women, who were tested for genital chlamydial infection in Institute of Public Health Kragujevac. Three screening tests were used: direct immunofluorescence (DIF) and rapid lateral immunochromatographic test (RT) for qualitative detection of chlamydial antigens and immunoenzyme (ELISA) test for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In addition, we found that the diagnostic performance varied greatly between different manufacturers who either use latex ICT or colloidal gold ICT for C. trachomatis . Although previous studies have shown that ICT has generally lower sensitivities compared to NAAT [ 14 , 15 ]. In China, the sensitivity of ICT varied from 21.2 % to 94.2 % in different regions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that the diagnostic performance varied greatly between different manufacturers who either use latex ICT or colloidal gold ICT for C. trachomatis . Although previous studies have shown that ICT has generally lower sensitivities compared to NAAT [ 14 , 15 ]. In China, the sensitivity of ICT varied from 21.2 % to 94.2 % in different regions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, among the sexually transmitted infections, Chlamydia trachomatis shows sharp geographical differences, but it occurs with a considerable frequency and should be screened more routinely in daily clinical practice. Therefore, although it is known that Chlamydia antibody tests have shown false positive and false negative results (17,18) and do not differentiate a current infection from immunological memory, Tosic-Pajic et al (18) consider the serological tests to be the most suitable screening method in terms of cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, and given the relatively avascular nature of the cornea in the presented case, we continued systemic therapy with ceftriaxone for 7 days. Complementary to systemic therapy and to prevent collagenase release from destructive corneal lesions [7] and manage any possible co-existing chlamydial infection [8], a systemic doxycycline was added. The intention behind this combined antibiotic therapy was also, apart from enhancing treatment efficacy, to avoid the potential development or spread of cephalosporin resistance [9].…”
Section: Discussionmentioning
confidence: 99%